Composition of Malay woodcarving : case studies on two traditional timber houses - Kamarudin, Zumahiran; Said, Ismail (Faculty of Built Environment, UTM, 2008)
Woodcarving is considered as an integral component to the vernacular Malay houses in the east coast of Peninsular Malaysia. The traditional timber houses are adorned with carving motifs of flora, calligraphy, geometry, fauna and cosmic features which are depicted according to the specified shape, size and dimension of wooden panel. This study presents an analysis of woodcarving in two prominent Malay houses, Mohamad Dobah and Hassan Mohd. Amin, both located in Kota Bahru, Kelantan. The methods of investigation include review of measured drawing reports of timber houses from the Centre for the Study of Built Environment in the Malay World (KALAM) at the Department of Architecture in the Universiti Teknologi Malaysia (UTM) and personal communication with two woodcarvers on art and crafts of woodcarving. The analysis revealed that Malay craftsmen applied several design qualities in making and fabricating their carvings into distinctive compositions. The qualities include visual attributes, ordering principles and craftsmen’s knowledge and skills on woodcarving. Besides these qualities, the meanings and significance of carved components are apparent with respect to its placement and configuration in interior as well as exterior fabrics of the timber houses. The ordering principles and visual attributes are considered as regulating factor that determines the beauty and meaning of the carved components and its relation to the house form and architectural elements. This is a suggestive indication of Malay craftsman’s mastery of skillfulness, intuition, ingenuity and creativity, logical thinking and wisdom in portraying visual composition and identity of woodcarving which emanate from crafts tradition.